Greater Reduction in Contralesional Hand Use After Frontoparietal Than Frontal Motor Cortex Lesions in Macaca mulatta - Darling, Warren G.; Pizzimenti, Marc A.; Rotella, Diane L.; Ge, Jizhi; Stilwell-Morecraft, Kimberly S.; Morecraft, Robert J. (Frontiers in Systems Neuroscience, 2021)
We previously reported that rhesus monkeys recover spontaneous use of the more impaired (contralesional) hand following neurosurgical lesions to the arm/hand representations of primary motor cortex (M1) and lateral premotor cortex (LPMC) (F2 lesion) when tested for reduced use (RU) in a fine motor task allowing use of either hand. Recovery occurred without constraint of the less impaired hand and with occasional forced use of the more impaired hand, which was the preferred hand for use in fine motor tasks before the lesion. Here we compared recovery of five F2 lesion cases in the same RU test to recovery after unilateral lesions of M1, LPMC, S1 and anterior portion of parietal cortex (F2P2 lesion – 4 cases). Average and highest %use of the contralesional hand in the RU task in F2 cases were twice that in F2P2 cases (p < 0.05). Recovery in the RU task was closely associated with volume and percentage of lesion to caudal (new) M1 (M1c) in both F2 and F2P2 lesion cases. One F2P2 case, with the largest M1c lesion and a large rostral somatosensory cortex (S1r) lesion developed severe contralesional hand nonuse despite exhibiting some recovery of fine motor function initially. We conclude that the degree of reduced use of the contralesional hand is primarily related to the volume of M1c injury and that severe nonuse requires extensive injury to M1c and S1r. Thus, assessing peri-Rolandic injury extent in stroke patients may have prognostic value for predicting susceptibility to RU and nonuse in rehabilitation.